2015
DOI: 10.3892/etm.2015.2242
|View full text |Cite
|
Sign up to set email alerts
|

Primary primitive neuroectodermal tumor arising in the mesentery and ileocecum: A report of three cases and review of the literature

Abstract: Primitive neuroectodermal tumor (PNET) is most commonly encountered in the soft tissue or bone in children and young adults, and its involvement in the intestines is exceedingly rare. To the best of our knowledge, eighteen cases have been reported to date. The present study reports three cases of PNET arising in the mesentery and ileocecum in 59- and 22-year-old males and a 36-year-old female. Computed tomography revealed a solid mass in the lower abdomen, with areas of cystic changes. Microscopically, the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The treatment of these tumors is based on a multimodal treatment combining local surgery and/or radiotherapy followed by multidrug systemic chemotherapy [31] [32] [33] [34]. Current chemotherapy regimens include combinations of vincristine, cyclophosphamide and doxorubicin [32]. The addition of ifosfamide and etoposide to a standard regimen significantly improves the outcome for patients with non metastatic Ewing's sarcoma a [45].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of these tumors is based on a multimodal treatment combining local surgery and/or radiotherapy followed by multidrug systemic chemotherapy [31] [32] [33] [34]. Current chemotherapy regimens include combinations of vincristine, cyclophosphamide and doxorubicin [32]. The addition of ifosfamide and etoposide to a standard regimen significantly improves the outcome for patients with non metastatic Ewing's sarcoma a [45].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery alone is associated with poor outcome. Therefore, enbloc resection with systemic adjuvant chemotherapy is primarily chosen for local and systemic control as for other ES/PNET 25. The longest reported survival was 204 months23 and the shortest was 3 months 26.…”
Section: Discussionmentioning
confidence: 99%
“…He observed that this highly aggressive, originally bone tumor was remarkably sensitive to radiation therapy. However extraskeletal cases are rare, several cases have been reported with different localisations, including -jejunum [1], chest wall [2], paravertebral region [3], stomach [4], lung parenchyma [5], breast tissue [6] and mesentery-ileocecum [7]. Soft tissue sarcomas encompass around 1% of all malignant tumors, but they are relatively more frequent in childhood and adolescent age [8], and extraskeletal Ewing sarcoma belongs to this group of tumors.…”
Section: Introductionmentioning
confidence: 99%